2011
DOI: 10.1142/s1084946711001811
|View full text |Cite
|
Sign up to set email alerts
|

Institutions and Entrepreneurial Intent: A Cross-Country Study

Abstract: This study examines a number of proposed relationships between formal and informal institutional factors that impact the entrepreneurial intent (EI) of 477 university business students in Germany, Russia and the United States, as well as similarities and differences in these relationships between countries. This is the first study, of which we are aware, to develop an instrument to measure the impact of formal institutional factors on EI based upon the World Bank's Doing Business Report. Overall, the results g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
66
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(75 citation statements)
references
References 47 publications
8
66
0
1
Order By: Relevance
“…Goethner et al () demonstrated that cooperation with industry has an indirect effect on entrepreneurial intention by affecting attitude toward entrepreneurial behavior. More generally, some scholars have proposed that regional environment, including the demographic, economic, structural, and political dimensions, as well as entrepreneurial dynamism, is an important determinant of attitude (Engle, Schlaegel, and Dimitriadi ; Kibler ).…”
Section: Proposed Model and Research Hypothesesmentioning
confidence: 99%
“…Goethner et al () demonstrated that cooperation with industry has an indirect effect on entrepreneurial intention by affecting attitude toward entrepreneurial behavior. More generally, some scholars have proposed that regional environment, including the demographic, economic, structural, and political dimensions, as well as entrepreneurial dynamism, is an important determinant of attitude (Engle, Schlaegel, and Dimitriadi ; Kibler ).…”
Section: Proposed Model and Research Hypothesesmentioning
confidence: 99%
“…In short, institutions are mental constructs that guide the actors' understanding of social phenomena and thus, set "the rules of the game" (North, 1990). Scholars of institutional theory argue that all strategic and economic activity is embedded in a social and normative context, and such a context motivates organizations and individuals to conform to social rules and expectations to be accorded legitimacy and support, or "a social license to operate" (Engle et al, 2011;North, 1990;Welter, 2011). Scott (1995) proposes a typology of formal and informal institutions, classifying them into regulatory, normative and cognitive categories.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…Remarkably, this extant body of knowledge is dominantly Western, Anglo-Saxon, mainly (Bullough et al 2014;Carey et al, 2010;Cassar, 2007;Cha and Bae, 2010;Crant, 1996;De Jorge-Moreno et al 2012;Paço et al 2011;Raijman, 2001;Souitaris et al 2007;Tegtmeier, 2006;Tomski, 2014;Turker and Sonmez Selcuk, 2009;Van Gelderen et al, 2008), and increasingly European (Castellano et al 2014;Llouga et al 2013;Nyock et al 2013;Tounés, 2006;Varela Villegas et al 2011), and/or cross-cultural (Cassar, 2007;Engle et al 2011;Laspita et al 2012;Liñán and Chen, 2009;Linón et al 2013;Moriano et al 2012;St-Jean et al, 2014). Empirical studies from Asia have appeared in recent years, from China (Bernhofer and Han, 2014;Siu and Lo, 2013), Pakistan (Azhar et al 2010), India (Wei, 2007), and Viet Nam (Tran and Santarelli 2014;Mai, 2016) In Shapero's Entrepreneurial Event Model (Shapero, 1975), it considers firm creation as the result of the interaction among contextual factors, which would act through their influences on the individual's perceptions.…”
Section: Introductionmentioning
confidence: 99%